Fireproof flame-retardant cable and preparation method thereof
By using pre-crosslinking and vulcanization treatment of butyl rubber, allyl modified phenolic resin and boron-doped composite filler in the cable sheath layer, the problem of flammability of the cable in the fire is solved, and the efficient flame retardant and excellent mechanical properties of the cable are achieved.
Patent Information
- Application Number
- CN202411746158.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the fire, the existing cables are decomposed at high temperatures to produce combustible low-molecular substances, which intensifies the fire and insufficient mechanical properties of the cable.
A sheath material including butyl rubber, allyl modified phenolic resin and boron doped composite filler is used to form a sheath layer with flame retardant, heat insulation and excellent mechanical properties through pre-crosslinking and vulcanization treatment.
The cable is not easy to burn at high temperatures, and a large amount of nitrogen-containing non-combustible gases are generated to prevent combustion. The cable's mechanical properties and fire resistance are significantly improved, making it less likely to crack.
Smart Images

Figure BDA0005163779780000081 
Figure BDA0005163779780000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a fire-proof and flame-retardant cable and a preparation method thereof. Background Art
[0002] Fireproof (fire-resistant) cable refers to a type of cable that can ensure the integrity of the line in the event of a fire. When the fire is hot, this type of cable can ensure that the cable continues to provide power and transmit various signals normally for a long time, thereby providing protection for fire control and lifesaving. It is especially meaningful for crowded public places or important places such as theaters, subways, airports, nuclear power plants, etc.
[0003] The sheath of the cable is mostly made of rubber. The existing rubber sheath can only play a buffering role. In the case of an accidental fire, the rubber will decompose into flammable low-molecular substances at high temperatures. The flammable low-molecular substances will quickly undergo a violent oxidation reaction with oxygen. The oxidation reaction releases a large amount of heat, which will further promote the decomposition of the rubber. At the same time, the products of the oxidation reaction, such as low-molecular alcohols and aldehydes, will also undergo an oxidation reaction with oxygen until the rubber is burned out. Summary of the invention
[0004] The object of the present invention is to provide a fire-resistant and flame-retardant cable and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a fire-retardant cable, comprising a cable core and a sheath layer, wherein the sheath material used for the sheath layer comprises the following components in parts by weight: 100 parts of butadiene rubber, 20 to 40 parts of allyl-modified phenolic resin, 15 to 25 parts of boron-doped composite filler, 0.5 to 1 part of vulcanizing agent, 1 to 3 parts of plasticizer, 0.5 to 1 part of accelerator, 1 to 3 parts of vulcanization activator, and 0.05 to 0.4 part of initiator; the preparation method of the sheath material is: melt-blending butadiene rubber, allyl-modified phenolic resin, boron-doped composite filler, and initiator at a processing temperature of 30 to 120° C. and a rotation speed of 30 to 150 rpm for 5 to 20 minutes, and then adding the vulcanizing agent, plasticizer, accelerator, and vulcanization activator at a processing temperature of 30 to 80° C. and a rotation speed of 30 to 150 rpm, and mixing for 5 to 10 minutes.
[0006] Furthermore, the vulcanizing agent is benzoyl peroxide or sulfur; the plasticizer is at least one of coumarone resin, dioctyl phthalate, tricresyl phosphate and diester of sebacate; the accelerator is one or more of sulfonamide TBBS, sulfonamide CBS, guanidine DPG, and thiuram TMTD; the vulcanization activator is zinc oxide and stearic acid, and the mass ratio thereof is 3:1; and the initiator is ammonium persulfate.
[0007] Furthermore, the cis content of the butadiene rubber is greater than or equal to 96% by weight.
[0008] Furthermore, the preparation method of the allyl-modified phenolic resin is as follows: first, 100 to 300 parts by weight of ordinary phenolic resin is mixed with 5 to 30 parts by weight of potassium hydroxide or sodium hydroxide, and then the mixture is reacted at 60 to 100° C. for 10 to 24 hours, and then 5 to 30 parts by weight of any one of 3-chloropropylene, 3-bromopropylene and 3-iodopropylene is added, and the mixture is reacted again at 60 to 100° C. for 10 to 24 hours, and then the mixture is extracted and purified to obtain the allyl-modified phenolic resin.
[0009] Furthermore, the preparation method of the boron-doped composite filler is as follows:
[0010] (1) Aluminum hydroxide powder with a particle size of 1 to 80 nm is uniformly dispersed in an 80 wt % ethanol aqueous solution, expanded perlite is added, and the two are put into a grinding jar for grinding. During the grinding process, the grinding jar is vacuumed. After grinding for 1 to 2 hours, an aminosilane coupling agent is added, and grinding is continued for 1 hour. The solid is filtered out, and dried at 105 to 110° C. to constant weight to obtain a modified expanded perlite composite material;
[0011] The invention uses wet grinding to modify expanded perlite, so that on one hand, the particle size of the expanded perlite is refined. The smaller the particles are, the more uniformly they are dispersed in the cable rubber material system. On the other hand, a nano-aluminum hydroxide powder dispersion solution is used as an environmental solvent during grinding. Due to the porous property of the expanded perlite, the nano-level aluminum hydroxide powder is filled into the holes and part of the pores are blocked, so that the heat convection in the pores is reduced, the heat reflection is increased, the thermal conductivity is reduced, and the thermal insulation effect is improved. In addition, an aminosilane coupling agent is added in the later stage of grinding to achieve the graft modification of the expanded perlite composite material.
[0012] (2) adding 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole and dichloromethane in sequence, adding triethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride at 0°C, adding the modified expanded perlite composite material under stirring at 40 rpm, increasing the stirring speed to 100 rpm, continuing the reaction for 3 to 5 hours, filtering, taking the solid, washing 3 to 5 times with a washing liquid, wherein the volume ratio of ethyl acetate to petroleum ether in the washing liquid is 1:3, and drying at 80°C to constant weight to obtain a pretreated composite material;
[0013] (3) The pretreated composite material, 100° C. water, and boric acid were mixed in a mass ratio of 3:6:1, the vacuum degree was adjusted to 0.08 MPa, ultrasonic reaction was carried out at 20 kHz for 4 to 6 hours, and the solid was filtered and dried at 80° C. to constant weight to obtain a boron-doped composite filler.
[0014] Furthermore, the amount of aluminum hydroxide powder in step (1) is 0.2% to 2% of the mass of the expanded perlite, the mass ratio of the expanded perlite to the 80wt% ethanol aqueous solution is 1:(3 to 6); and the amount of the aminosilane coupling agent is 0.2% to 2% of the mass of the expanded perlite.
[0015] Furthermore, the particle size of the expanded perlite in step (1) is 0.5-4 mm, and the surface pore size of the expanded perlite is larger than the particle size of the aluminum hydroxide powder.
[0016] Furthermore, the aminosilane coupling agent in step (1) is any one of KH540, KH550 or KH792.
[0017] Furthermore, in step (2), the molar ratio of 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole, triethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 0.5:1:1.5:1; and the ratio of 1-hydroxybenzotriazole, modified expanded perlite composite material, and dichloromethane is 0.1 g:0.07 g to 0.2 g:15 mL.
[0018] Furthermore, a method for preparing a fire-retardant cable comprises the following steps:
[0019] S1: 10 tinned copper wires with a diameter of 1-1.5mm are twisted into a copper core, and an insulating rubber is extruded to form an insulating layer with a thickness of 1.6mm. Then, a metal aluminum foil with a thickness of 0.1mm is wrapped around the outer surface of the insulating layer to form a shielding layer with a thickness of 0.5-1.0mm to obtain a cable core; the insulating rubber is ordinary EPDM rubber insulating material;
[0020] S2: A sheath layer is extruded on the outside of the cable core with a sheath material. The cable is heated to 130-160°C by microwave for vulcanization. The vulcanization temperature of 130-160°C is maintained and the cable is further vulcanized by hot air vulcanization equipment. The line speed is 40-60m / min. The thickness of the sheath layer is 1.4mm, and a fire-retardant cable is obtained.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] The modified expanded perlite composite material and 4,5-dihydroxy-2-hexenoic acid are combined by generating an amide bond, and the two are combined with boric acid by relying on its hydroxyl group to achieve boron doping, forming a nitrogen-boron synergistic flame retardant system. During combustion, pyrolysis produces a large amount of nitrogen-containing non-flammable gas, H2O(g), etc., which prevents the combustion from continuing. Then, it is pre-crosslinked with butadiene rubber and allyl-modified phenolic resin containing double bonds by relying on double bonds, which increases the crosslinking active points on the molecular chain and thus improves the crosslinking activity. On the one hand, it reduces the amount of later vulcanizers and vulcanization accelerators, and on the other hand, it improves the mechanical properties of the sheath material. Mechanical properties, thereby optimizing the mechanical properties of the cable. In addition, the construction of the pre-crosslinking system inserts flame retardant materials such as boron-doped composite materials and allyl-modified phenolic resin into the three-dimensional network cross-linking structure, which not only improves the flame retardant stability and dispersion stability of the material, but also further improves the density of the flame retardant and fireproof outer jacket layer, so that it has good mechanical properties and fire resistance, and is not easy to crack. At the same time, the modified expanded perlite composite material uses the pre-crosslinking structure to form an insulating network, so that the prepared sheath mixture has excellent thermal insulation and heat resistance, thereby improving the fire resistance of the cable. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the fire-retardant cables prepared in the following examples.
[0025] Flame retardant: The self-extinguishing time parameter is measured by the UL-94 method, and the oxygen index parameter is measured by the GB / T10707-89 method.
[0026] High temperature resistance: Use a ventilation heat aging oven to test the cable at 100℃ for 60 days. After aging for 60 days (d), measure the cable insulation resistance. Generally, the engineering requires that the cable insulation resistance should not be less than 1MΩ / kV. The cable is considered to have passed the high temperature resistance test. Then apply 6.0kV AC to the heat-aged cable for 20 minutes. If no arc or breakdown occurs, it means that the cable has passed the test.
[0027] Mechanical properties: The tensile strength and elongation at break were tested using ASTM D412 standard.
[0028] Example 1
[0029] A method for preparing a fire-resistant and flame-retardant cable, characterized in that it comprises the following steps:
[0030] S1: 10 tinned copper wires with a diameter of 1mm are twisted into a copper core, and an insulating rubber is extruded to form an insulating layer with a thickness of 1.6mm. Then, a metal aluminum foil with a thickness of 0.1mm is wrapped around the outer surface of the insulating layer to form a shielding layer with a thickness of 1.0mm to obtain a cable core; the insulating rubber is ordinary EPDM rubber insulation material;
[0031] S2: Extruding a sheath layer with sheath material outside the cable core, heating the cable to 130-160°C by microwave for vulcanization, maintaining the vulcanization temperature of 130-160°C and continuing to vulcanize the cable with hot air vulcanization equipment, the thickness of the sheath layer is 1.4mm, and a fire-retardant cable is obtained;
[0032] The preparation method of the sheath material is as follows: 100 parts by weight of butadiene rubber, 20 parts by weight of allyl modified phenolic resin, 15 parts by weight of boron-doped composite filler, and 0.05 parts by weight of ammonium persulfate are melt-blended at a processing temperature of 80° C. and a rotation speed of 150 rpm for 15 minutes, and then 0.5 parts by weight of sulfur, 1 part by weight of tricresol phosphate, 0.5 parts by weight of sulfonamide TBBS, and 1 part by weight of a vulcanizing activator are added at a processing temperature of 40° C. and a rotation speed of 80 rpm, and kneaded for 5 minutes; the vulcanizing activator is zinc oxide and stearic acid, and the mass ratio thereof is 3:1.
[0033] The preparation method of the allyl-modified allyl-modified phenolic resin is as follows: firstly, 100 parts by weight of ordinary phenolic resin and 10 parts by weight of sodium hydroxide are mixed, and then the mixture is reacted at 80° C. for 15 hours, and then 12 parts by weight of 3-bromopropylene are added, and the mixture is reacted at 80° C. for 15 hours, and then the mixture is extracted and purified to obtain the allyl-modified phenolic resin;
[0034] The preparation method of the boron-doped composite filler is as follows:
[0035] (1) Aluminum hydroxide powder with a particle size of 35 nm is uniformly dispersed in an 80 wt % ethanol aqueous solution, expanded perlite is added, and the two are put into a grinding jar for grinding. During the grinding process, the grinding jar is vacuumized. After grinding for 1 hour, a silane coupling agent KH550 is added, and the grinding is continued for 1 hour. The solid is filtered and dried at 105° C. to constant weight to obtain a modified expanded perlite composite material; the amount of aluminum hydroxide powder is 0.2% of the mass of the expanded perlite, and the mass ratio of the expanded perlite to the 80 wt % ethanol aqueous solution is 1:3; the amount of silane coupling agent KH550 is 0.2% of the mass of the expanded perlite; the particle size of the expanded perlite is 0.5 mm, and the surface pore size of the expanded perlite is larger than the particle size of the aluminum hydroxide powder;
[0036] (2) 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole and dichloromethane were added in sequence, triethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added at 0°C, and the modified expanded perlite composite material was added under stirring at 40 rpm. The stirring speed was increased to 100 rpm, and the reaction was continued for 3 hours. The solid was filtered and washed 4 times with washing liquid, wherein the volume ratio of ethyl acetate to petroleum ether in the washing liquid was 1:3, and the solid was dried at 80°C to constant weight to obtain a pretreated composite material; the molar ratio of 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole, triethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was 0.5:1:1.5:1; the ratio of 1-hydroxybenzotriazole, modified expanded perlite composite material and dichloromethane was 0.1 g:0.07 g:15 mL;
[0037] (3) The pretreated composite material, 100° C. water, and boric acid were mixed in a mass ratio of 3:6:1, the vacuum degree was adjusted to 0.08 MPa, ultrasonic reaction was carried out at 20 kHz for 4 h, and the solid was filtered and dried at 80° C. to constant weight to obtain a boron-doped composite filler.
[0038] Example 2
[0039] The difference between Example 2 and Example 1 is as follows, and the remaining steps are the same as Example 1: the preparation method of the sheath material is: 100 parts by weight of butadiene rubber, 26 parts by weight of allyl modified phenolic resin, 18 parts by weight of boron-doped composite filler, and 0.1 parts by weight of ammonium persulfate are melt-blended at a processing temperature of 80°C and a rotation speed of 150rpm for 15min, and then 0.5 parts by weight of sulfur, 1 part by weight of diester of sebacic acid, 0.5 parts by weight of guanidine DPG, and 1 part by weight of vulcanizing activator are added at a processing temperature of 40°C and a rotation speed of 80rpm, and mixed for 5min; the vulcanizing activator is zinc oxide and stearic acid, and the mass ratio thereof is 3:1;
[0040] The preparation method of the boron-doped composite filler is as follows:
[0041] (1) Aluminum hydroxide powder with a particle size of 50 nm is uniformly dispersed in an 80 wt % ethanol aqueous solution, expanded perlite is added, and the two are put into a grinding jar for grinding. During the grinding process, the grinding jar is vacuumized. After grinding for 1 hour, a silane coupling agent KH540 is added, and the grinding is continued for 1 hour. The solid is filtered and dried at 105° C. to constant weight to obtain a modified expanded perlite composite material; the amount of aluminum hydroxide powder is 0.8% of the mass of the expanded perlite, and the mass ratio of the expanded perlite to the 80 wt % ethanol aqueous solution is 1:4; the amount of silane coupling agent KH540 is 0.8% of the mass of the expanded perlite; the particle size of the expanded perlite is 1.6 mm, and the surface pore size of the expanded perlite is larger than the particle size of the aluminum hydroxide powder;
[0042] (2) 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole and dichloromethane were added in sequence, triethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added at 0°C, and the modified expanded perlite composite material was added under stirring at 40 rpm. The stirring speed was increased to 100 rpm, and the reaction was continued for 3 hours. The solid was filtered and washed 4 times with washing liquid, wherein the volume ratio of ethyl acetate to petroleum ether in the washing liquid was 1:3, and the solid was dried at 80°C to constant weight to obtain a pretreated composite material; the molar ratio of 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole, triethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was 0.5:1:1.5:1; the ratio of 1-hydroxybenzotriazole, modified expanded perlite composite material and dichloromethane was 0.1 g:0.1 g:15 mL;
[0043] (3) The pretreated composite material, 100°C water, and boric acid were mixed in a mass ratio of 3:6:1, the vacuum degree was adjusted to 0.08 MPa, ultrasonic reaction was performed at 20 kHz for 4 h, and the solid was filtered and dried at 80°C to constant weight to obtain a boron-doped composite filler.
[0044] Example 3
[0045] The difference between Example 3 and Example 1 is as follows, and the remaining steps are the same as Example 1: the preparation method of the sheath material is: 100 parts by weight of butadiene rubber, 33 parts by weight of allyl modified phenolic resin, 21 parts by weight of boron-doped composite filler, and 0.28 parts by weight of ammonium persulfate are melt-blended at a processing temperature of 80°C and a rotation speed of 150rpm for 15min, and then 0.7 parts by weight of benzoyl peroxide, 1 part by weight of tricresol phosphate, 0.7 parts by weight of sulfonamide CBS, and 2 parts by weight of vulcanizing activator are added at a processing temperature of 40°C and a rotation speed of 80rpm, and kneaded for 5min; the vulcanizing activator is zinc oxide and stearic acid, and the mass ratio thereof is 3:1;
[0046] The preparation method of the boron-doped composite filler is as follows:
[0047] (1) Aluminum hydroxide powder with a particle size of 65 nm is uniformly dispersed in an 80 wt % ethanol aqueous solution, expanded perlite is added, and the two are put into a grinding jar for grinding. During the grinding process, the grinding jar is vacuumized. After grinding for 1.5 h, a silane coupling agent KH792 is added, and the grinding is continued for 1 h. The solid is filtered and dried at 105° C. to constant weight to obtain a modified expanded perlite composite material; the amount of aluminum hydroxide powder is 1.4% of the mass of the expanded perlite, and the mass ratio of the expanded perlite to the 80 wt % ethanol aqueous solution is 1:5; the amount of silane coupling agent KH792 is 1.4% of the mass of the expanded perlite; the particle size of the expanded perlite is 2.8 mm, and the surface pore size of the expanded perlite is larger than the particle size of the aluminum hydroxide powder;
[0048] (2) 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole and dichloromethane were added in sequence, triethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added at 0°C, and the modified expanded perlite composite material was added under stirring at 40 rpm. The stirring speed was increased to 100 rpm, and the reaction was continued for 4 hours. The solid was filtered and washed 4 times with washing liquid. The volume ratio of ethyl acetate to petroleum ether in the washing liquid was 1:3. The solid was dried at 80°C to constant weight to obtain a pretreated composite material. The molar ratio of 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole, triethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was 0.5:1:1.5:1. The ratio of 1-hydroxybenzotriazole, modified expanded perlite composite material and dichloromethane was 0.1 g:0.15 g:15 mL.
[0049] (3) The pretreated composite material, 100° C. water, and boric acid were mixed in a mass ratio of 3:6:1, the vacuum degree was adjusted to 0.08 MPa, ultrasonic reaction was carried out at 20 kHz for 5 h, and the solid was filtered and dried at 80° C. to constant weight to obtain a boron-doped composite filler.
[0050] Example 4
[0051] The difference between Example 4 and Example 1 lies in the following steps, and the remaining steps are the same as Example 1: the preparation method of the sheath material is as follows: 100 parts by weight of butadiene rubber, 40 parts by weight of allyl modified phenolic resin, 25 parts by weight of boron-doped composite filler, and 0.1 parts by weight of ammonium persulfate are melt-blended at a processing temperature of 80° C. and a rotation speed of 150 rpm for 15 minutes, and then 1 part by weight of benzoyl peroxide, 2 parts by weight of dioctyl phthalate, 0.7 parts by weight of sulfonamide TBBS, and 1 part by weight of vulcanizing activator are added at a processing temperature of 40° C. and a rotation speed of 80 rpm, and kneaded for 5 minutes; the vulcanizing activator is zinc oxide and stearic acid, and the mass ratio thereof is 3:1;
[0052] The preparation method of the boron-doped composite filler is as follows:
[0053] (1) Aluminum hydroxide powder with a particle size of 80 nm is uniformly dispersed in an 80 wt % ethanol aqueous solution, expanded perlite is added, and the two are put into a grinding jar for grinding. During the grinding process, the grinding jar is vacuumized. After grinding for 2 h, a silane coupling agent KH550 is added, and the grinding is continued for 1 h. The solid is filtered and dried at 105° C. to constant weight to obtain a modified expanded perlite composite material; the amount of aluminum hydroxide powder is 2% of the mass of the expanded perlite, and the mass ratio of the expanded perlite to the 80 wt % ethanol aqueous solution is 1:6; the amount of silane coupling agent KH550 is 2% of the mass of the expanded perlite; the particle size of the expanded perlite is 4 mm, and the surface pore size of the expanded perlite is larger than the particle size of the aluminum hydroxide powder;
[0054] (2) 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole and dichloromethane were added in sequence, triethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added at 0°C, and the modified expanded perlite composite material was added under stirring at 40 rpm. The stirring speed was increased to 100 rpm, and the reaction was continued for 5 hours. The solid was filtered and washed 5 times with washing liquid, wherein the volume ratio of ethyl acetate to petroleum ether in the washing liquid was 1:3, and the solid was dried at 80°C to constant weight to obtain a pretreated composite material; the molar ratio of 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole, triethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was 0.5:1:1.5:1; the ratio of 1-hydroxybenzotriazole, modified expanded perlite composite material and dichloromethane was 0.1 g:0.2 g:15 mL;
[0055] (3) The pretreated composite material, 100° C. water, and boric acid were mixed in a mass ratio of 3:6:1, the vacuum degree was adjusted to 0.08 MPa, ultrasonic reaction was carried out at 20 kHz for 6 h, and the solid was filtered and dried at 80° C. to constant weight to obtain a boron-doped composite filler.
[0056] Comparative Example 1
[0057] The difference between Comparative Example 1 and Example 1 is that no aluminum hydroxide powder is added, and the remaining steps are the same as Example 1.
[0058] Comparative Example 2
[0059] The difference between Comparative Example 2 and Example 1 is that no silane coupling agent is added, and the remaining steps are the same as Example 1.
[0060] Comparative Example 3
[0061] The difference between Comparative Example 3 and Example 1 is that 4,5-dihydroxy-2-hexenoic acid is not added, and the remaining steps are the same as Example 1.
[0062] Comparative Example 4
[0063] The difference between Comparative Example 4 and Example 1 is that boric acid is not added, and the remaining steps are the same as Example 1.
[0064] Comparative Example 5
[0065] The difference between Comparative Example 5 and Example 1 is that butadiene rubber, allyl-modified phenolic resin, boron-doped composite filler, ammonium persulfate, sulfur, tricresyl phosphate, sulfonamide TBBS, and vulcanization activator are mixed together, and the remaining steps are the same as Example 1.
[0066] Comparative Example 6
[0067] The difference between Comparative Example 6 and Example 1 is that no allyl modified phenolic resin is added, and the remaining steps are the same as Example 1.
[0068] Effect example
[0069] Table 1 below shows the performance analysis results of the cables using Examples 1 to 4 of the present invention and Comparative Examples 1 to 6.
[0070] Table 1
[0071]
[0072]
[0073] The present invention combines the modified expanded perlite composite material with 4,5-dihydroxy-2-enoic acid and boric acid to achieve boron doping and form a nitrogen-boron synergistic flame retardant system. During combustion, pyrolysis produces a large amount of nitrogen-containing non-combustible gas, H2O(g), etc., which prevents the combustion from continuing. Then, the modified expanded perlite composite material is pre-crosslinked with butadiene rubber and allyl-modified phenolic resin containing double bonds by relying on double bonds, thereby improving the mechanical properties of the sheath material and further optimizing the mechanical properties of the cable. In addition, the construction of the pre-crosslinking system inserts flame-retardant materials such as boron-doped composite materials and allyl-modified phenolic resin into the three-dimensional network cross-linking structure, which not only improves the flame retardant stability and dispersion stability of the material, but also further improves the compactness of the flame retardant and fireproof outer jacket layer, so that it has good mechanical properties and fire resistance and is not easy to crack. At the same time, the modified expanded perlite composite material forms a heat-insulating network with the help of the pre-crosslinking structure, so that the prepared sheath mixture has both excellent thermal insulation and heat resistance, thereby improving the fire resistance of the cable.
[0074] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A fire-retardant cable, comprising a cable core and a sheath layer, characterized in that: The sheath material used in the sheath layer includes the following components in parts by weight: 100 parts of butadiene rubber, 20-40 parts of allyl modified phenolic resin, 15-25 parts of boron doped composite filler, 0.5-1 parts of vulcanizing agent, 1-3 parts of plasticizer, 0.5-1 parts of accelerator, 1-3 parts of vulcanization activator, and 0.05-0.4 parts of initiator; The preparation method of the sheath material is as follows: butadiene rubber, allyl modified phenolic resin, boron doped composite filler and initiator are melt-blended at a processing temperature of 30 to 120° C. and a rotation speed of 30 to 150 rpm for 5 to 20 minutes, and then a vulcanizer, a plasticizer, an accelerator and a vulcanization activator are added at a processing temperature of 30 to 80° C. and a rotation speed of 30 to 150 rpm, and mixed for 5 to 10 minutes.
2. A fire-resistant and flame-retardant cable according to claim 1, characterized in that: The vulcanizing agent is benzoyl peroxide or sulfur; the plasticizer is at least one of coumarone resin, dioctyl phthalate, tricresyl phosphate and diester of sebacate; the accelerator is one or more of sulfonamide TBBS, sulfonamide CBS, guanidine DPG and thiuram TMTD; the vulcanization activator is zinc oxide and stearic acid in a mass ratio of 3:1; and the initiator is ammonium persulfate.
3. A fire-resistant and flame-retardant cable according to claim 1, characterized in that: The cis content of the butadiene rubber is greater than or equal to 96 weight %.
4. A fire-resistant and flame-retardant cable according to claim 1, characterized in that: The preparation method of the boron-doped composite filler is as follows: (1) Aluminum hydroxide powder with a particle size of 1 to 80 nm is uniformly dispersed in an 80 wt % ethanol aqueous solution, expanded perlite is added, and the two are put into a grinding jar for grinding. During the grinding process, the grinding jar is vacuumed. After grinding for 1 to 2 hours, an aminosilane coupling agent is added, and grinding is continued for 1 hour. The solid is filtered out, and dried at 105 to 110° C. to constant weight to obtain a modified expanded perlite composite material; (2) adding 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole and dichloromethane in sequence, adding triethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride at 0°C, adding the modified expanded perlite composite material under stirring at 40 rpm, increasing the stirring speed to 100 rpm, continuing the reaction for 3 to 5 hours, filtering, taking the solid, washing 3 to 5 times with a washing liquid, wherein the volume ratio of ethyl acetate to petroleum ether in the washing liquid is 1:3, and drying at 80°C to constant weight to obtain a pretreated composite material; (3) The pretreated composite material, 100° C. water, and boric acid were mixed in a mass ratio of 3:6:1, the vacuum degree was adjusted to 0.08 MPa, ultrasonic reaction was carried out at 20 kHz for 4 to 6 hours, and the solid was filtered and dried at 80° C. to constant weight to obtain a boron-doped composite filler.
5. A fire-resistant and flame-retardant cable according to claim 4, characterized in that: The amount of aluminum hydroxide powder in step (1) is 0.2% to 2% of the mass of the expanded perlite, the mass ratio of the expanded perlite to the 80wt% ethanol aqueous solution is 1:(3 to 6); the amount of the aminosilane coupling agent is 0.2% to 2% of the mass of the expanded perlite.
6. A fire-resistant and flame-retardant cable according to claim 4, characterized in that: The particle size of the expanded perlite in step (1) is 0.5-4 mm, and the surface pore size of the expanded perlite is larger than the particle size of the aluminum hydroxide powder.
7. A fire-resistant and flame-retardant cable according to claim 4, characterized in that: The aminosilane coupling agent in step (1) is any one of KH540, KH550 or KH792.
8. The fire-resistant and flame-retardant cable according to claim 4, characterized in that: In step (2), the molar ratio of 4,5-dihydroxy-2-hexenoic acid, 1-hydroxybenzotriazole, triethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 0.5:1:1.5:1; the ratio of 1-hydroxybenzotriazole, modified expanded perlite composite material, and dichloromethane is 0.1 g:0.07 g to 0.2 g:15 mL.
9. A method for preparing a fire-resistant and flame-retardant cable according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: 10 tinned copper wires with a diameter of 1-1.5mm are twisted into a copper core, and an insulating rubber is extruded to form an insulating layer with a thickness of 1.6mm. Then, a metal aluminum foil with a thickness of 0.1mm is wrapped around the outer surface of the insulating layer to form a shielding layer with a thickness of 0.5-1.0mm to obtain a cable core; the insulating rubber is ordinary EPDM rubber insulating material; S2: A sheath layer is extruded on the outside of the cable core with a sheath material. The cable is heated to 130-160°C by microwave for vulcanization. The vulcanization temperature of 130-160°C is maintained and the cable is further vulcanized by hot air vulcanization equipment. The line speed is 40-60m / min. The thickness of the sheath layer is 1.4mm, and a fire-retardant cable is obtained.
Citation Information
Cited By
Cable insulation fireproof layer and preparation method and application thereof
CN120842852A